A three-dimensional finite element analysis of tuning the selected acoustic helicoidal resonator by the change of its mandrel diameter. (1st January 2022) - Łapka, Wojciech
Abstract: This work presents the possibility of tuning the acoustic helicoidal resonator by the change of it's central mandrel diameter. Set of numerically computed systems with different mandrel diameters were executed. For numerical investigations, by the use of a finite element method, the acoustic helicoidal resonator was placed inside an infinite long cylindrical duct. Also the transmission loss is achieved as an acoustic attenuation performance parameter. The results show that the mandrel is a very important part of the helicoidal resonator and it provides a proper physical functioning of this solution, as an acoustic resonator. Also this paper presents the normalized range of mandrel diameters, which provides the best performance.